Inner shell as variation key of local hard clam Meretrix spp. - Hamli, Hadi; Idris, Mohd Hanafi; Mustafa Kamal, Abu Hena; Rajaee, Amy Halimah; Arshad, Aziz (Triveni Enterprises, 2016)
The morphology and 12 shell morphometric features proportionate to shell length were analysed between local hard clam; Meretrix lyrata, M. meretrix and M. lusoria from Sarawak, Malaysia. Meretrix spp. was observed to comprise a unique feature of a pallial sinus scar for each species. Analysis of variance revealed significant differences among Meretrix spp. using proportion ratios of SL for SW; LL; AL; LCT; AW; PW and PS (p<0.05). Cluster analysis among morphometric features of M. lyrata, M. meretrix and M. lusoria were discriminated at 98.5% similarities and supported by the principal component analysis. The present study suggests that pallial sinus scar shape, together with interior and exterior morphometric features, were suitable as identification keys for Meretrix spp. Hence, the present study emphasizes on the application of interior, rather than exterior morphology and morphometric features in hard clam identification before further investigation can be performed through genetic identification means.